2016
DOI: 10.1088/1752-7155/10/2/026012
|View full text |Cite
|
Sign up to set email alerts
|

Cancerous glucose metabolism in lung cancer—evidence from exhaled breath analysis

Abstract: Cancer cells prefer hyperglycolysis versus oxidative phosphorylation, even in the presence of oxygen. This phenomenon is used through the FDG-PET scans, and may affect the exhaled volatile signature. This study investigates the volatile signature in lung cancer (LC) before and after an oral glucose tolerance test (OGTT) to determine if tumor cells' hyperglycolysis would affect the volatile signature. Blood glucose levels and exhaled breath samples were analyzed before the OGTT, and 90 min after, in both LC pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…Hence, there is clearly an unmet need for noninvasive screening test to detect asymptomatic patients at an early stage of disease. Five untargeted on-line studies using PTR [197][198][199] and IMS 200,201 reported VOCs for diagnostic purposes in early stage lung cancer. One study reported lowered concentrations of isoprene acetone and methanol in patients with lung cancer.…”
Section: Lung Cancermentioning
confidence: 99%
“…Hence, there is clearly an unmet need for noninvasive screening test to detect asymptomatic patients at an early stage of disease. Five untargeted on-line studies using PTR [197][198][199] and IMS 200,201 reported VOCs for diagnostic purposes in early stage lung cancer. One study reported lowered concentrations of isoprene acetone and methanol in patients with lung cancer.…”
Section: Lung Cancermentioning
confidence: 99%
“…Among these pathways, glucose metabolism is studied intensively because this pathway is widely used by cancer cells to provide building blocks and to acquire therapeutic resistance (11)(12)(13). LC exhibits a feature of hyperactive glucose metabolism as verified by metabolomic studies and clinical PET-CT examinations (8,14). Glucose transporters, including GLUT1 and GLUT3, are found to be upregulated in LC cells to support their increased glucose uptake (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…These changes in cellular metabolism favour survival in an oxygen deprived environment and result in altered metabolic intermediates that function as the building blocks for new cells, both enabling the growth of rapidly dividing cancer cells, and also altering the profile of VOCs in breath [ 9 ]. As these processes are fundamental to cancer cell survival, such altered cellular metabolism occurs as one of the earliest stages of tumourigenesis [ 10 12 ], hence VOCs are excellent candidate biomarkers for early detection of cancer.…”
Section: Breath Biomarkers For Early Detection Of Cancermentioning
confidence: 99%